A Comparative Cytogenetic Analysis of 2 Bothriuridae Species and Overview of the Chromosome Data of Scorpiones - Schneider, Marielle C. [UNESP]; Zacaro, Adilson A.; Pinto-Da-Rocha, Ricardo; Candido, Denise M.; Cella, Doralice M. [UNESP] (Oxford University Press, 2009)
The order Scorpiones is one of the most cytogenetically interesting groups within Arachnida by virtue of the combination of chromosome singularities found in the 59 species analyzed so far. In this work, mitotic and meiotic chromosomes of 2 species of the family Bothriuridae were detailed. This family occupies a basal position within the superfamily Scorpionoidea. Furthermore, review of the cytogenetic data of all previously studied scorpions is presented. Light microscopy chromosome analysis showed that Bothriurus araguayae and Bothriurus rochensis possess low diploid numbers compared with those of species belonging to closely related families. Gonadal cells examined under light and in transmission electron microscopy revealed, for the first time, that the Bothriuridae species possess typical monocentric chromosomes, and male meiosis presented chromosomes with synaptic and achiasmatic behavior. Moreover, in the sample of B. araguayae studied, heterozygous translocations were verified. The use of techniques to highlight specific chromosomal regions also revealed additional differences between the 2 Bothriurus species. The results herein recorded and the overview elaborated using the available cytogenetic information of Scorpiones elucidated current understanding regarding the processes of chromosome evolution that have occurred in Bothriuridae and in Scorpiones as a whole.
Keywords: achiasmatic meiosis; diploid number; synaptonemal complex; translocation